Dietary intake and nutritional status of Korean children and adolescents: a review of national survey data - Minji Kang; So Yoon Choi; Minyoung Jung (The Korean Pediatric Society, 2021)
In Korea, several national cross-sectional surveys monitor the diet, nutritional status, and health status of children. This continual dedicated national surveillance system contributes to the identification of nutritional and health issues, establishment of public health policies, and development of nutrition recommendations. This paper provides recent information about the Korea National Health and Nutrition Examination Survey and the Korean Youth Risk Behavior Web-based Survey and describes key nationwide survey findings published in the last 5 years on infant feeding practices and the dietary intake and nutritional status of Korean infants, children, and adolescents. There have been increasing trends in children, and teenagers who skip breakfast, eat fast food, consume sugary drinks, have vitamin D deficiency, and are obese. This review will inform pediatricians, nutritionists, and other health care practitioners who track children's growth and development. It may also help researchers and policymakers identify diet-related policies and strategies for chronic disease prevention in Korean infants, children, and adolescents.